2000
DOI: 10.1128/iai.68.5.3040-3047.2000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological and Phylogenetic Associations of Two Novel Putative Virulence Genes, iha and iroN E. coli , among Escherichia coli Isolates from Patients with Urosepsis

Abstract: Two novel putative Escherichia coli virulence genes, iha and iroN from E. coli (iroN E. coli ), were detected in 55 and 39%, respectively, of 67 E. coli isolates from patients with urosepsis. iha and iroN E. coli exhibited divergent associations with other putative virulence genes, phylogenetic markers, host characteristics, and antimicrobial resistance.The virulent strains of Escherichia coli that cause urinary tract infections (UTIs) and other extraintestinal infections in humans (i.e., extraintestinal patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
103
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 30 publications
7
103
1
3
Order By: Relevance
“…Johnson et al found that iha was present in 55% of urosepsis isolates and was more prevalent in isolates from immunocompetent hosts, suggesting that Iha confers some pathogenic advantage [12]. In a different study, Johnson et al found that presence of iha predicted multiple same-strain recurrences of urinary tract infections (UTI) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al found that iha was present in 55% of urosepsis isolates and was more prevalent in isolates from immunocompetent hosts, suggesting that Iha confers some pathogenic advantage [12]. In a different study, Johnson et al found that presence of iha predicted multiple same-strain recurrences of urinary tract infections (UTI) [13].…”
Section: Introductionmentioning
confidence: 99%
“…The primers and PCR conditions were previously described (1,2,4,7,12,15,16). Amplicons identities were confirmed by sequencing (Amersham Pharmacia Biotech).…”
mentioning
confidence: 99%
“…Iha is a potentially important accessory virulence factor for several pathotypes of E. coli, including STEC, UPEC and avian-pathogenic strains (Ewers et al, 2007;Johnson et al, 2000;Ons et al, 2007;Rodriguez-Siek et al, 2005;Touati, 2000), functioning as an adhesin and, at least for UPEC, as a catecholate siderophore receptor (Leveille et al, 2006). This latter function is consistent with the fact that iha is induced under iron-limiting conditions and is subject to Fur-mediated repression in iron-replete environments in both UPEC and O157:H7 STEC strains (Leveille et al, 2006;Rashid et al, 2006b), as well as in the hyper-virulent LEE-negative STEC strain 98NK2, as shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Among STEC a range of novel adhesins have been identified, including the chromosomally encoded adherence-conferring protein Iha, a homologue of Vibrio cholera IrgA . Iha was first characterized in E. coli O157:H7, but it is distributed widely among LEEnegative and LEE-positive STEC, as well as in uropathogenic E. coli (UPEC) (Johnson et al, 2000;Tarr et al, 2000). Tarr et al (2000) reported that an iha deletion mutant of O157:H7 STEC was impaired in adherence to HeLa cells, although the difference did not reach statistical significance.…”
Section: Introductionmentioning
confidence: 99%